Experimental Analysis of Simplified Rules Fuzzy Logic Speed Controller for Wide Speed Range Operations - Md Hairul Nizam Talib; Z. Ibrahim; Z. Rasin; J.Mat Lazi; M. Azri; N.S.Y. Farah (Institute of Advanced Engineering and Science, 2018)
This paper presents the experimental analysis of simplified rules Fuzzy Logic Speed Controller (FLSC) of Induction Motor drive. The maximum gain of input scaling factor, FLSC is generally limited by the coverage of universe of discoursed (UoD). Thus, to further increase the input gain scaling factor, the outer membership function need to be increased. This analysis covers various values in the range of UoD values from [-1,1] to [-5,5] for the wide speed range operations from low to rated speed ranges. The FLSC is employed to the indirect Field Oriented Control method fed by a voltage source inverter. Simulation and experimental verification is done by using Matlab/Simulink and dSPACE 1103 controller experimental rigs respectively. Based on the results, speed performance behaviours are improved over the wide speed range operations in term of rise time and setting time. The tuning approached is simple without additional algorithm for faster and more accurate response.